2021
DOI: 10.4314/ahs.v21i1.3s
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life and associated factors among HIV patients on antiretroviral therapy in North West region of Cameroon

Abstract: Background: There is evidence that Quality of Life (QoL) of People Living with HIV/AIDS (PLHIV) has a significant role in ART retention, treatment adherence, and survival. As a result, QoL is becoming increasingly important for policy- makers, program implementers, and researchers. However, factors associated with QoL, in a culturally diverse country like Cameroon are unknown. Objective: We aimed to assess the QoL of PLHIV on ART and assess the extent to which physical, psychosocial, environ- mental, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
5
2
Order By: Relevance
“…This finding is consistent with another study conducted in Iran that reported the overall mean QOL of PLWHA who are on ART was 39.13% [ 22 ] and a study from Ghana (38.3%) [ 23 ]. However, this review pooled estimate is higher than the estimate reported by studies conducted in western Africa Cameron (28.6%) [ 24 ], Nigeria (33.4%) [ 25 ] and Ghana (11.39%) [ 26 ]. This discrepancy might be observed due to variability in socio-cultural aspects, clinical status of the participants, study design, and better patient care in previous studies.…”
Section: Discussioncontrasting
confidence: 82%
“…This finding is consistent with another study conducted in Iran that reported the overall mean QOL of PLWHA who are on ART was 39.13% [ 22 ] and a study from Ghana (38.3%) [ 23 ]. However, this review pooled estimate is higher than the estimate reported by studies conducted in western Africa Cameron (28.6%) [ 24 ], Nigeria (33.4%) [ 25 ] and Ghana (11.39%) [ 26 ]. This discrepancy might be observed due to variability in socio-cultural aspects, clinical status of the participants, study design, and better patient care in previous studies.…”
Section: Discussioncontrasting
confidence: 82%
“…Tunisia. Although moderate, the overall mean scores of QoL domains were higher than that reported by Khademi et al In Iran, 10 but lower compared to the study of Osei-Yeboah et al in Ghana, 25 Busi et al in Cameroon, 29 Liping et al in China 37 and Nobre et al in Finland. 38 In fact, the lowest mean scores of QoL were recorded for the social relations, the environment and the psychological domains and the highest mean scores were noted for the physical, the level of independence and the spiritual domains.…”
Section: Discussioncontrasting
confidence: 61%
“…They are, particularly, low or very low in some African and Middle East countries Unemployment and financial issues affect negatively people's social relation, the level of independence and mental health, as well. [26][27][28] Some studies reported a better perception of QoL in clients receiving ART 29,30 and other findings confirmed the benefits of ART initiated at 1 month and 4 months 31 and one year 13 after clients' enrolment, compared to ART naïve clients with symptoms and AIDS-related comorbidities. 25 In fact, people receiving ART reported better physical function that positively affects their level of independence.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…A systematic review of PLHIV in sub-Saharan Africa found pooled estimates of anxiety and depression to be 32% and 9%, respectively [ 14 , 15 ]. Psychological symptoms usually lead to nonadherence to ART, poor rating of QoL and increased HIV-related deaths [ 16 ]. In North America and Europe, evidence showed that a positive HIV test result alone and the perception of life changes associated with a life-threatening, chronic illness led to episodes of depression and anxiety [ 13 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%